2013
DOI: 10.1093/schbul/sbt050
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Discontinuity in Psychosis: A Combined Study of Cortical Gyrification and Functional Connectivity

Abstract: The point of rarity in brain structure and function that separates the 2 major psychotic disorders-schizophrenia and bipolar disorder-is presently unknown. The aim of this study is to combine surface anatomical and functional imaging modalities to quantify the integrity of cortical connectivity in pursuit of the neural basis of the Kraepelinian "line of divide." We tested the hypothesis that multimodal brain regions show overlapping abnormalities in both disorders, while schizophrenia-specific defects are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
76
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 41 publications
18
76
1
Order By: Relevance
“…When cognitive tasks are demanded, "non-specialized" brain regions must be recruited to meet the cognitive demands, resulting in excessive and inefficient recruitment. Several task-related fMRI studies in schizophrenia give support to this perspective (Potkin et al, 2009;Liddle et al, 2013;Palaniyappan and Liddle, 2014). The present results of increased FCS in the DMN suggest that "non-specialized" recruitment exists even when the patients are at rest.…”
Section: Discussionsupporting
confidence: 77%
“…When cognitive tasks are demanded, "non-specialized" brain regions must be recruited to meet the cognitive demands, resulting in excessive and inefficient recruitment. Several task-related fMRI studies in schizophrenia give support to this perspective (Potkin et al, 2009;Liddle et al, 2013;Palaniyappan and Liddle, 2014). The present results of increased FCS in the DMN suggest that "non-specialized" recruitment exists even when the patients are at rest.…”
Section: Discussionsupporting
confidence: 77%
“…Several fMRI studies of task performance in patients support this notion. [47][48][49] We observed that in siblings, though the ADF is perturbed, there is some degree of recovery or compensation. Though long links are reduced in proportion, there is a degree of strengthening of relationship among the existing links, which is not seen in patients.…”
Section: Discussionmentioning
confidence: 80%
“…Details of the LGI computation process can be found in the validation paper [12], previous studies in psychiatric patients [13,16,42] and at https://surfer.nmr.mgh.harvard.edu/fswiki/LGI. Briefly, an outer envelope that tightly wraps the pial cortical surface is created before local measurement of circular GI is computed for …”
Section: Local Gyrification Index (Lgi)mentioning
confidence: 99%